Literature Review : Factors Affecting Birth Weight and its Management - Indrawati, Nuke Devi; Dewi, Maria Ulfah Kurnia; Mustika, Dian Nintyasari; Puspitaningrum, Dewi (Gaster, 2024)
The literature review has the aim of reviewing and comparing the similarities of several research results regarding the factors that influence the occurrence of low birth weight babies and their management methods in several hospitals in Indonesia. Literature review method with this study was carried out by conducting a literature review by searching several national journals. Literature search using several keywords, namely "low birthweight (LBW)", "infants", "management of LBW" for 10 literature publications from 2012-2022. Article searches used Sciencedirect, Garuda Portal, Mendeley and Google Scholar for articles with quantitative and qualitative designs. Results Of the ten articles stated that LBW occurs not only in premature babies but normal babies can also experience LBW. LBW is not only influenced by the mother's knowledge but other factors such as nutrition, pregnancy interval, age, parity, lifestyle, and pregnancy complications. Discussion and Conclusion: Here the role of health workers and parents in handling LBW is very important without having to be expensive and can be done at home so that it can help increase LBW with exclusive breastfeeding, prevent hypothermia, prevent infection and keep the baby healthy so that stunting does not occur.